A liquid chromatographic method, with fluorometric detection, for the determination of enrofloxacin and ciprofloxacin in plasma and endometrial tissue of mares - González, Claudia (2006)
The aim of this work was to develop and validate a simple and sensitive analytical method for determining enrofloxacin (EFX) and ciprofloxacin (CFX) in equine plasma and endometrial tissue samples, as a precursor to conducting pharmacokinetic/pharmacodynamic studies on equine endometritis This was achieved in the form of a liquid chromatographic procedure, with fluorometric detection, which also gave good separation of other fluoroquinolones including marbofloxacin (MFX), danofloxacin (DFX) and ofloxacin (OFX). Analytes were separated on a C18 reversed phase column using an acidified mobile phase. The exact composition of the mobile phase differed for plasma (16% acetonitrile:methanol [13:1,v/v] 84% water containing 0.4% triethylamine and 0.4% phosphoric acid [35%]) and endometrial tissue (14% acetonitrile, 86% water, without methanol) samples. EFX and CFX were both detected at excitation and emission wavelengths of 294 and 500 nm, respectively. Prior to chromatography, EFX and CFX were purified by solid phase extraction from plasma, and a combination of solvent/solid phase extraction from endometrial tissue. Mean absolute recoveries for EFX and CFX from plasma were 94.1 and 78.0%, respectively, and from endometrial tissue, 78.0 and 57.8%, respectively, with a percentage residual standard deviation (%R.S.D.) <10% in each case. Mean relative recoveries for EFX and CFX from plasma were 91.3 and 119.4%, respectively, and from endometrial tissue, 80.2 and 108.0%, respectively, with a %R.S.D. <20% in each case. Standard curves constructed using blank plasma and endometrial tissue samples, spiked with authentic EFX and CFX in the ranges 0.005–10.0 μg mL−1 and 0.05–10.0 μg g−1, respectively, all showed acceptable linearity with correlation coefficients, r2 ≥ 0.977. Mean intra- and inter-day precision (expressed as %R.S.D.) was <6 and <13%, respectively, with an associated accuracy (expressed as percentage relative error, %R.E.) of <20% for both analytes in both matrices. Acceptable precision and accuracy was also demonstrated at the pre-assigned LOQs of 0.005 μg mL−1 for both EFX and CFX in plasma, and 0.05 μg g−1 for both drugs in endometrial tissue. EFX and CFX were stable in both plasma and endometrial tissue for at least 60 days at −20 °C.